2018
DOI: 10.1103/physrevmaterials.2.111402
|View full text |Cite
|
Sign up to set email alerts
|

Origin of skyrmion lattice phase splitting in Zn-substitutedCu2OSeO3

Abstract: We present an investigation into the structural and magnetic properties of Zn-substituted Cu 2 OSeO 3 , a system in which the skyrmion lattice (SkL) phase in the magnetic field-temperature phase diagram was previously seen to split as a function of increasing Zn concentration. We find that splitting of the SkL is only observed in polycrystalline samples and reflects the occurrence of several coexisting phases with different Zn content, each distinguished by different magnetic behavior. No such multiphase behav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
6
20
3
Order By: Relevance
“…entropic effects arising from the non-magnetic substitution 32 , which may also explain the long formation times. However, it is also possible that Zn substitution does not change the skyrmion formation physics, and it is simply a reduction of the lower boundary of the skyrmion region from 55.5 K in pristine Cu 2 OSeO 3 to 52.5 K in our Zn substituted sample 31 that lengthens the formation time. Extrapolating our zero electric field data to 55.5 K, we would expect a formation time of 2.1 +4.6 −0.9 ns, which is too short to observe with SANS.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…entropic effects arising from the non-magnetic substitution 32 , which may also explain the long formation times. However, it is also possible that Zn substitution does not change the skyrmion formation physics, and it is simply a reduction of the lower boundary of the skyrmion region from 55.5 K in pristine Cu 2 OSeO 3 to 52.5 K in our Zn substituted sample 31 that lengthens the formation time. Extrapolating our zero electric field data to 55.5 K, we would expect a formation time of 2.1 +4.6 −0.9 ns, which is too short to observe with SANS.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, crystals of (Cu 1−x Zn x ) 2 OSeO 3 (x = 0 to 0.024) have been grown and shown to host similar skyrmion phases to pristine Cu 2 OSeO 3 , but at temperatures shifted slightly lower as the Zn substitution level is increased 31 . Notably, the lifetime of metastable skyrmions in Zn substituted crystals is dramatically enhanced compared to that seen in pristine Cu 2 OSeO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A single crystal of Cu 2 OSeO 3 was grown from pre-reacted polycrystalline powder using chemical vapour transport with TeCl 4 as a transporting agent (Details can be found in the supplemental information of Ref. [38]). An FEI Helios nano lab dual-beam was used to prepare 200 nm thick lamellae with lateral dimensions of 4 x 6 µm in [100] and [110] orientations.…”
Section: Experiments Detailsmentioning
confidence: 99%
“…It has further been shown that the position of the skyrmion pocket can be tuned through controlled chemical substitution [33][34][35]. In Cu 2 OSeO 3 , the substitution of Cu ions with nonmagnetic Zn ions led to a shift of the whole phase diagram towards lower temperatures [33].…”
Section: Introductionmentioning
confidence: 99%
“…It has further been shown that the position of the skyrmion pocket can be tuned through controlled chemical substitution [33][34][35]. In Cu 2 OSeO 3 , the substitution of Cu ions with nonmagnetic Zn ions led to a shift of the whole phase diagram towards lower temperatures [33]. On the other hand, magnetic doping with Ni induced an increase of the size of the skyrmion pocket towards lower temperatures with increasing Ni substitution, reported for polycrystalline samples studied with both ac susceptibility [34] and SANS [35].…”
Section: Introductionmentioning
confidence: 99%